PENGARUH PERSEPSI RISIKO DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN GULA TROPICANA SLIM YANG DIMEDIASI OLEH SIKAP KONSUMEN DI WILAYAH DKI JAKARTA - Hanny Chandra; Tony Sitinjak (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2021)
Sugar is a carbohydrate that can be directly absorbed by the body to convert into energy. However, now people tend to avoid sugar with a sugar free diet. Currently there is a low calorie sugar brand name Tropicana Slim. This research is to find out the influence of Perceived Risk and Brand Image on Purchase Decision Tropicana Slim sugar mediated by Consumer Attitude in DKI Jakarta religion. Data were collected by distributing questionnaires to 165 respondents who had bought and consumed Tropicana Slim sugar. Sampling technique using judgment sampling method. Data analysis technique in this research are validity and reliability test, descriptive analysis, likert scale, multiple linear regression analysis, evaluation of structural model. The analysis tools on this study used WarpPLS 6.0 and SPSS 20.0. The results of the analysis show that Risk Perception have negative influence on Consumer Attitude, Brand Image have positive influence on Consumer Attitude, Risk Perception have negative influence on Purchase Decision, Brand Image have positive influence on Purchase Decision, Consumer Attitudes have positive influence on Purchase Decision, Consumer Attitude cannot mediate the effect of Risk Perception on Purchase Decision, Consumer Attitudes can mediate the influence of Brand Image on Purchase Decision. Keywords: Perceived Risk, Brand Image, Consumer Attitude, Purchase Decision